High-Dialysate-Glucose-Induced Oxidative Stress and Mitochondrial-Mediated Apoptosis in Human Peritoneal Mesothelial Cells. (5th May 2014) - Hung, Kuan-Yu; Liu, Shin-Yun; Yang, Te-Cheng; Liao, Tien-Ling; Kao, Shu-Huei
Abstract : Human peritoneal mesothelial cells (HPMCs) are a critical component of the peritoneal membrane and play a pivotal role in dialysis adequacy. Loss of HPMCs can contribute to complications in peritoneal dialysis. Compelling evidence has shown that high-dialysate glucose is a key factor causing functional changes and cell death in HPMCs. We investigated the mechanism of HPMC apoptosis induced by high-dialysate glucose, particularly the role of mitochondria in the maintenance of HPMCs. HPMCs were incubated at glucose concentrations of 5 mM, 84 mM, 138 mM, and 236 mM. Additionally, N-acetylcysteine (NAC) was used as an antioxidant to clarify the mechanism of high-dialysate-glucose-induced apoptosis. Exposing HPMCs to high-dialysate glucose resulted in substantial apoptosis with cytochrome c release, followed by caspase activation and poly(ADP-ribose) polymerase cleavage. High-dialysate glucose induced excessive reactive oxygen species production and lipid peroxidation as well as oxidative damage to DNA. Mitochondrial fragmentation, multiple mitochondrial DNA deletions, and dissipation of the mitochondrial membrane potential were also observed. The mitochondrial dysfunction and cell death were suppressed using NAC. These results indicated that mitochondrial dysfunction is one of the main causes of high-dialysate-glucose-induced HPMC apoptosis.